THE IMPACT OF ARTIFICIAL INTELEGENC, STRATEGY BUSINESS AND QUALITY PRODUCT TO ORGANIZATION BUSINESS - Indah Kusumawati; Rokhmat Subagiyo (ZILLZELL MEDIA PRIMA, 2025)
This study evaluates the relationship between organizational culture, business strategy, and organizational performance in companies in Jakarta, Indonesia, as the largest tourism industrial area in ASEAN. The study highlights that organizational culture that includes discipline, innovation, and a clear division of authority, as well as a business strategy that focuses on vision, mission, tactics, and marketing, has a significant influence on organizational performance, as measured through growth, customer satisfaction, and marketing effectiveness. Of the 384 respondents, the results showed that organizational culture and business strategy significantly influenced organizational performance, both individually and collectively. In addition, this study also analyzes the role of artificial intelligence (AI) and product quality on the performance of Micro, Small, and Medium Enterprises (MSMEs). Using SPSS for analysis, the results show that AI has an influence of 85%, product quality by 75%, and the combination of the two contributes 80% to the performance of MSMEs, with the remaining 20% influenced by other factors not analyzed in this study. These findings underscore that higher AI adoption and improved product quality significantly improve the performance of MSMEs, providing a positive projection for the growth of small businesses in the community. This research makes an important contribution to understanding how organizational culture, business strategy, and technology and product quality can be the main driving factors in improving the performance of organizations and MSMEs, especially in the tourism and small business sectors in Indonesia.